Chronic Rapamycin Prevents Electrophysiological and Morphological Alterations Produced by Conditional Pten Deletion in Mouse Cortex - Jason S. Hauptman; Joseph Antonios; Gary W. Mathern; Michael S. Levine; Carlos Cepeda (Cells)
Abnormalities in the mammalian target of the rapamycin (mTOR) pathway have been implicated in numerous developmental brain disorders. While the molecular and histological abnormalities have been described, less is known about alterations in membrane and synaptic excitability with chronic changes in the mTOR pathway. In the present study, we used a conditional mouse model with a deletion of the phosphatase and tensin homologue (Pten-/-, a negative regulator of mTOR) from cortical pyramidal neurons (CPNs). Whole-cell patch clamp recordings in ex vivo slices examined the intrinsic and synaptic membrane properties of layer II/III CPNs in normal mice treated with rapamycin for four weeks, and Pten-/- mice with and without chronic treatment with rapamycin. Compared with control mice, CPNs from Pten-/- mice demonstrated increased membrane capacitance and time constant in association with increased neuronal somatic size, reduced neuronal firing, and decreased frequency of spontaneous and miniature inhibitory postsynaptic currents, consistent with decreased pre-synaptic GABA release. Rapamycin treatment for four weeks prevented these changes in Pten-/- mice. CPNs from normal mice chronically treated with rapamycin, compared with CPNs from naïve mice, showed reduced capacitance and time constant, increased input resistance, and changes in inhibitory synaptic inputs, consistent with increased pre-synaptic GABA release. These results support the concept that Pten deletion results in significant changes in inhibitory inputs onto CPNs, and these alterations can be prevented with chronic rapamycin treatment. In addition, normal mice treated with rapamycin also display altered membrane and synaptic properties. These findings have potential implications for the treatment of neurological disorders associated with mTOR pathway dysfunction, such as epilepsy and autism.